2010
DOI: 10.1186/1755-7682-3-27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of productivity of hospitals in Botswana: a DEA application

Abstract: BackgroundBotswana national health policy states that the Ministry of Health shall from time to time review and revise its organization and management structures to respond to new developments and challenges in order to achieve and sustain a high level of efficiency in the provision of health care. Even though the government clearly views assuring efficiency in the health sector as one of its leadership and governance responsibilities, to date no study has been undertaken to measure the technical efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 30 publications
3
39
1
3
Order By: Relevance
“…Also, the study included 17 out of the 18 (94 %) regional referral hospitals active during the study period. The sample size for a similar study in Eritrea [4] comprised 19 out of 20 hospitals (95 %) this number is not very much different from the sample size in our study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Also, the study included 17 out of the 18 (94 %) regional referral hospitals active during the study period. The sample size for a similar study in Eritrea [4] comprised 19 out of 20 hospitals (95 %) this number is not very much different from the sample size in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Since 2000 studies have been undertaken in a number of countries, including Angola [2], Namibia [3], Botswana [4], Zambia [5] Kenya [6, 26], Benin [27], Burkina Faso [28], Ethiopia [29], Ghana [3032], Nigeria [33], Seychelles [34], Sierra Leone [35, 36], South Africa [7, 37], Uganda [18] and Eritrea [38]. These studies demonstrate that DEA is an important tool for policy advice.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the inability of this methodology to identify the underlying causes of inefficiencies. In Botswana, there are few studies assessing efficiency of public hospitals (10,11). Using DEA, Tlotlego et al (11) concluded that over 70% of the hospitals were run inefficiently between 2006 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In Botswana, there are few studies assessing efficiency of public hospitals (10,11). Using DEA, Tlotlego et al (11) concluded that over 70% of the hospitals were run inefficiently between 2006 and 2008. An earlier study by Ramanathan et al (10) identified inefficient health districts and hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Technical efficiency is defined as the ratio of personnel output to input.It deals with a combination of data which produce certain output. Concerning this type of efficiency‚ the main question to be asked is if the highest degree of output is obtained considering each personnel output to input (Tlotlego et al‚ 2010). …”
Section: Introductionmentioning
confidence: 99%